Activism, Textuality, and Feedback in La nueva banda de la terraza’s Graffiti- Projections - Guerrero Hernandez, Juan Carlos (Street Art & Urban Creativity, 2023)
In the social mobilizations (2020-2022) during and after the COVID-19 lockdown in Colombia, the graffiti- projections produced, projected, and published by La nueva banda de la terraza played an essential role in visualizing, nurturing, and accompanying the social protests and the demands. As part of an unparalleled visual activism in Colombia, the graffiti-projections, which began in Medellín and soon expanded to other cities and beyond the country’s borders, created an expanded para-cinema of protests, played an essential role in a complex web of actions and practices that made it possible, for the first time in the republican history of Colombia, to create a comprehensive, multivocal, and diverse social movement. The present analysis discusses how the graffiti- projections catalyzed engagement and dialogue and strengthened the democratization of the public sphere by developing an expanded para-cinema that involved textuality and social media, reenergized graffiti, street art, and communal Do-It-With-Others, and developed emancipatory strategies and networks.